2020
DOI: 10.1016/j.eneco.2020.104664
|View full text |Cite
|
Sign up to set email alerts
|

Public-private partnerships investment in energy as new determinant of CO2 emissions: The role of technological innovations in China

Abstract: This paper explores the relationship between 'public-private partnerships investment in energy sector and carbon emissions' considering the vital role of technological innovations in carbon emissions function for China. In doing so, we apply bootstrapping autoregressive distributed lag modeling (BARDL) for examining the cointegration between carbon emissions and its determinants. The empirical results reveal that public-private partnerships investment in energy impedes environmental quality by increasing carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
199
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 466 publications
(229 citation statements)
references
References 78 publications
27
199
2
1
Order By: Relevance
“…Further, Dauda et al (2019) also found that technological advancement plays a significant role in pollution reduction. Our results are also in line with the studies of (Fernández et al, 2018;Long et al, 2018;Shahbaz et al, 2020;H. Wang & Ang, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Further, Dauda et al (2019) also found that technological advancement plays a significant role in pollution reduction. Our results are also in line with the studies of (Fernández et al, 2018;Long et al, 2018;Shahbaz et al, 2020;H. Wang & Ang, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…cointegrating relationship among all the variables in the presence of structural breaks. These cointegration findings in some form are supported by the earlier studies like Hasanov et al (2018) and Shahbaz et al (2020).…”
Section: Resultssupporting
confidence: 86%
“…Technological innovation refers to the process of initial commercialization of new products, new processes, and new technologies [36], which achieve high-quality economic development and environmental pollution control by reducing carbon emissions and promoting the development of new energy [37], [38]. Koç ak and Ulucak [39] indicated that R&D expenditures could reduce CO 2 emissions.…”
Section: C.innovation and Environmental Issuementioning
confidence: 99%